The Effect Of Motivation, Work Discipline, And Work Environment On The Performance Of Employees At Pt Telkom City Hall In Makassar City - Thoriq Baharsyah; Fariz Fariz (JURNAL ECONOMINA, 2026)
This study aims to determine the effect of work motivation, work discipline, and work environment on employee performance at PT Telkom Balaikota in Makassar City. This study uses a quantitative approach with a causal associative research type. The study population was 117 employees, with a sample of 91 respondents determined using the Slovin formula and simple random sampling techniques. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression, t-test, and F-test. The results showed that work motivation had a positive and significant effect on employee performance with a t-value of 4.045 and a significance of 0.000. Work discipline had a positive and significant effect with a t-value of 5.190 and a significance of 0.000. The work environment also had a positive and significant effect with a t-value of 2.745 and a significance of 0.007. Simultaneously, work motivation, work discipline, and work environment had a positive and significant effect on employee performance with an F-value of 80.307 and a significance of 0.000. Thus, increasing work motivation, work discipline, and work environment can encourage increased employee performance.